2018
DOI: 10.1016/j.redox.2018.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Identification of homocysteine-suppressive mitochondrial ETC complex genes and tissue expression profile – Novel hypothesis establishment

Abstract: Hyperhomocysteinemia (HHcy) is an independent risk factor for cardiovascular disease (CVD) which has been implicated in matochondrial (Mt) function impairment. In this study, we characterized Hcy metabolism in mouse tissues by using LC-ESI-MS/MS analysis, established tissue expression profiles for 84 nuclear-encoded Mt electron transport chain complex (nMt-ETC-Com) genes in 20 human and 19 mouse tissues by database mining, and modeled the effect of HHcy on Mt-ETC function. Hcy levels were high in mouse kidney/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 85 publications
0
26
0
3
Order By: Relevance
“…29,30 p27 can block the cell cycle in G0/G1 phase by negatively regulation of cyclin/CDK complexes, and PCNA is a well-known molecular marker for cell proliferation because of the role of replication in S phase, which could coordinate with p27 in the regulation of cell cycle. 31,32 In this study, we found 100 μmol/L Hcy was also used in other studies 33,34 to explore the effects of Hcy on VSMCs proliferation and human aortic smooth muscle cells (HASMC) mitochondrial dysfunction and it was showed The pathogenesis of atherosclerosis involves changes in the expression and function of a series of genes, and VSMCs proliferation is precisely regulated by various proliferation related genes, particularly the mitogenic genes. MFN2 is a newly discovered cell proliferation inhibitor that localize in the mitochondrial outer membrane and it plays an essential role in mitochondrial fusion, mitochondrial morphology in mammalian cells, yeasts, and flies.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 p27 can block the cell cycle in G0/G1 phase by negatively regulation of cyclin/CDK complexes, and PCNA is a well-known molecular marker for cell proliferation because of the role of replication in S phase, which could coordinate with p27 in the regulation of cell cycle. 31,32 In this study, we found 100 μmol/L Hcy was also used in other studies 33,34 to explore the effects of Hcy on VSMCs proliferation and human aortic smooth muscle cells (HASMC) mitochondrial dysfunction and it was showed The pathogenesis of atherosclerosis involves changes in the expression and function of a series of genes, and VSMCs proliferation is precisely regulated by various proliferation related genes, particularly the mitogenic genes. MFN2 is a newly discovered cell proliferation inhibitor that localize in the mitochondrial outer membrane and it plays an essential role in mitochondrial fusion, mitochondrial morphology in mammalian cells, yeasts, and flies.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of the current study is to evaluate extended HM cycle gene expression in disease conditions, which is a different strategy compared with our previous database mining studies. In our previous studies, we examined tissue expression profile of 12 core HM cycle genes and 97 genes in the mitochondrial electron transport chain (ETC) complexes in 20 normal human and 19 normal mouse tissues [54,57]. We established the correlation of gene expression with HM cycle metabolites, including Hcy, SAM, SAH and SAM/SAH ratio in mice [54,57] and examined differential gene expression among different cell types and tissues [58].…”
Section: Discussionmentioning
confidence: 99%
“…1A) [53]. These datasets were analyzed utilizing GEO2R from GEO databases as we previously described [52,54]. Differentially expressed genes were defined as p -value ≤ 0.05 and absolute fold change ≥2.…”
Section: Methodsmentioning
confidence: 99%
“…Hcy-mediated hypomethylation of DNA and histone modifications impair epigenetic control of gene expression and may contribute to pathogenesis of various HHcy-related human diseases [ 18 ]. Recent comprehensive data mining analyses in human and mouse tissues revealed that 15 nuclear-encoded genes for ETC complex proteins are suppressed in HHcy [ 94 ]. Among the identified genes, eleven were of ETC complex I, one of complex IV and two of complex V. Since 4 of the 11 Hcy-suppressed genes of complex I encode core subunits, which are indispensable for activity, the authors suggest that dysfunction of complex I due to alterations in gene expression may play a primary role in Hcy-induced pathogenicity.…”
Section: Homocysteine and Mitochondrial Oxidative Stressmentioning
confidence: 99%